Preparation and surface-functionalization of dye-doped bioconjugated poly(styrene-co-maleimide) nanoparticles - Swanepoel, Andri (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2014.